2011
DOI: 10.1371/journal.pone.0024139
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Ranking and Toxic Mode of Action Evaluation of Commonly Used Agricultural Adjuvants on the Basis of Bacterial Gene Expression Profiles

Abstract: The omnipresent group of pesticide adjuvants are often referred to as “inert” ingredients, a rather misleading term since consumers associate this term with “safe”. The upcoming new EU regulation concerning the introduction of plant protection products on the market (EC1107/2009) includes for the first time the demand for information on the possible negative effects of not only the active ingredients but also the used adjuvants. This new regulation requires basic toxicological information that allows decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 25 publications
0
27
0
1
Order By: Relevance
“…The steep dose−response curve of acute lethality caused by F3-NE2a is similar to that caused by surfactant-like compounds that act via a narcosis mode of action. 43,44 Because NAs are surfactants, it has been suggested that narcosis is the mode of acute toxicity of OSPW. 43,45 Acute toxicity of fractions from the esterifiable and acid-extractable fraction of OSPW also displayed a steep dose−response, similar to characteristics of surfactants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The steep dose−response curve of acute lethality caused by F3-NE2a is similar to that caused by surfactant-like compounds that act via a narcosis mode of action. 43,44 Because NAs are surfactants, it has been suggested that narcosis is the mode of acute toxicity of OSPW. 43,45 Acute toxicity of fractions from the esterifiable and acid-extractable fraction of OSPW also displayed a steep dose−response, similar to characteristics of surfactants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Most of the surfactants used in the formulation of GBHs are designed to accelerate the movement of glyphosate across plant surface membranes and also foster the movement of glyphosate into mammalian cells [31,35]. Many co-formulants are more toxic than technical glyphosate [31,36] and synergistic activity may occur in some exposure scenarios with certain formulations. Accordingly, differential toxicity arises from variable combinations of the innate toxicity of the surfactant(s) in a GBH compared to technical glyphosate, the impact of the surfactant(s) on the movement of glyphosate through human skin and into cells, and possible synergistic impacts [30,[37][38][39].…”
Section: Differential Toxicitymentioning
confidence: 99%
“…Such mechanisms are often studied under conditions of high exposures corresponding to application levels in the field. High levels of xenobiotics strongly impact organism physiology and defense responses, by inducing molecular injury and damages (Teixeira et al, 2007 ; Ramel et al, 2009 ; Das et al, 2010 ; Nobels et al, 2011 ; Gomes et al, 2014 ), mainly related to oxidative stress, membrane disruption, lipid peroxidation, protein damage, or DNA damage. In contrast, few studies deal with the responses to conditions of low exposure to pesticides in a context of runoff or residual contaminations.…”
Section: Introductionmentioning
confidence: 99%